Macroinvertebrates Distribution In Spatially Heterogeneous Gravel-Bed Rehabilitated River Reach - Arsad, Azamuddin (2016)
Spatially heterogeneous bed is a dominant bedforms in gravel-bed channel of natural channels. Macroinvertebrates are among the first organism to resettle in newly rehabilitated channel. This study explores the macroinvertebrates distribution in relation with physical habitat and hydraulic properties of riffle–pool bedforms, particularly the variations in hydraulic performance on different bed oscillation morphologies. Information from the study reach at downstream of Sungai Batu Sebelah where the river was rehabilitated was used to illustrate the approach of this study. A hydrodynamic model was developed to reflects base flow discharge of the study reach. The hydrodynamic model have been sucessfully calibrated with correlation coefficient R = 0.991 at the upstream, and correlation coefficient R = 0.994 at the downstream. Validation for the model have found the correlation between the model predicted values are very close with the values from field measurement and calculational approach, with value of correlation coefficient R = 0.999 to R = 1. Biotic data shows pollution sensitive makroinvertebrata from the order of Ephemeroptera, Plecoptera and Trichoptera (EPT) such as Baetis sp., Caenis sp., Heptageniidae, Leptophlebiidae, dan Hydropsyche sp. were found at the study reach. The biotic data confirmed that the water qualirt at the upstream of the study reach to be in Class II as showed through Water Quality Indeks in the Interim National Water Quality Standard , which the water quality was classed as suitable for sensitive aquatic species. Values of shear stress from the hydrodynamic model were tested against the preferred shear stress by the macroinvertebrates that were found at the study reach. Result shows that the existence of benthic macroinvertebrates is associated with the hydraulics condition in which the organisms makes its home.